PENGARUH WORK-FAMILY CONFLICT (WFC) DAN WORKPLACE STRESS (WPS) TERHADAP BURNOUT DENGAN PERCEIVED SUPERVISOR SUPPORT (PSS) SEBAGAI VARIABEL MODERASI (Studi Pada Perawat Perempuan RSUD ULIN Banjarmasin di Ruangan ICU, IGD dan Hemodialisa): Studi Pada Perawat Perempuan RSUD ULIN Banjarmasin di Ruangan ICU, IGD dan Hemodialisa - Devi Anita Filayanti Oetoyo (JWM (JURNAL WAWASAN MANAJEMEN), 2022)
This research aims to find out and analyze the influence of work-family conflict on burnout, the influence of workplace stress on burnout, the influence of perceived supervisor support on burnout, the role of perceived supervisor support on the influence of work-family conflict on burnout, and the role of perceived supervisor support on the influence of workplace stress on burnout in female nurses at Ulin Hospital Banjarmasin in the ICU, IGD and Hemodialysis Room. This research is quantitative research with an explanatory research approach. This research method uses a questionnaire with 86 populations, and all of them were determined as samples as respondents. The measurement of variables used Interval Scale and Likert Scale technique with the weights scale from 1 to 5. The data were analyzed using Partial Least Square (PLS). The results of this indicated that (i) there was a significant positive influence of work-family conflict on burnout, (ii) there was a significant positive influence of workplace stress on burnout, (iii) there was a significant positive influence of perceived supervisor support on burnout, (iv) there was a significant negative influence of perceived supervisor support as the moderating variable on the influence of work-family conflict on burnout, and (v) there was a significant positive influence of perceived supervisor support as a moderating variable on the influence of workplace stress on burnout. Keywords : Work-Family Conflict, Workplace Stress, Perceived Supervisor Support, Burnout